2022
DOI: 10.1101/2022.12.14.22283422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Re-evaluating progression and pathways followingMycobacteria tuberculosisinfection within the spectrum of tuberculosis disease

Abstract: Background: Traditional understanding of the risk of progression fromMycobacterium tuberculosis(Mtb) infection to tuberculosis (TB) disease overlooks nuance across a spectrum of disease. Methods: We developed a deterministic model ofMtbinfection and minimal (pathological damage but not infectious), subclinical (infectious but no reported symptoms), and clinical (infectious and symptomatic) TB disease, informed by a rigorous evaluation of data from a systematic review of TB natural history. Using a Bayesian app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…[ 27 ] A minority of those infected (currently only inferred by conversion to positive immunoreactivity following exposure) will develop disease. [ 28 , 29 ] While Mtb infection was assumed to be lifelong in the classic framework, evidence now suggests that a substantial proportion of individuals self-clear infection. [ 30 , 31 ] Existing estimates for the proportion of people with Mtb infection are based on immunoreactivity, [ 32 ] likely leading to an overestimate.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27 ] A minority of those infected (currently only inferred by conversion to positive immunoreactivity following exposure) will develop disease. [ 28 , 29 ] While Mtb infection was assumed to be lifelong in the classic framework, evidence now suggests that a substantial proportion of individuals self-clear infection. [ 30 , 31 ] Existing estimates for the proportion of people with Mtb infection are based on immunoreactivity, [ 32 ] likely leading to an overestimate.…”
Section: Resultsmentioning
confidence: 99%
“…LTBI is an otherwise asymptomatic condition. Whenever it has been in the crosshairs of clinical or population health research and practice, it has mainly been in relation to its potential progression to active TB, and the resultant individual morbidity and population transmission of M.tb (1), (2), (3), (40). Here we showed that LTBI is independently associated with worse overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with Mycobacterium tuberculosis (M.tb) is characterized by an immunopathological spectrum (1), (2), (3), (4), (5). Clinically overt or active TB disease is often associated with a prolonged systemic inflammatory response with symptomatic tissue destruction and remodeling (6).…”
Section: Introductionmentioning
confidence: 99%
“…This is evident when using the time since recent travel as the starting point for assessing disease progression, rather than the original time of migration into a low-incidence country. If the high TB rate among migrants is indeed driven by recent exposure, incidence curves using recent travel as follow-up start should better reflect estimated rates of disease onset post-exposure, as demonstrated here [ 9 ].…”
Section: Discussionmentioning
confidence: 99%